Breeding biology of guppy fish, Poecilia reticulata (Peters, 1859) in the laboratory - Shahjahan, Reza Md; Ahmed, Md Jubayer; Begum, Rowshan Ara; Rashid, Md Abdur (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The breeding biology of guppy fish, Poecilia reticulata (Cyprinodontiformes: Poiciliidae) was studied during March 2008 to May 2009 in Zoological garden laboratory, Curzon Hall campus, Dhaka University. Guppy bred all over the year except in the winter months December and January with a peak period in July. They were viviparous and multiple breeders, i.e., give birth to fry several times in the breeding season. The mean egg diameter was measured to be (1.02±0.08mm) and fecundity was estimated (40-89) per gram of body weight. The gestation period ranged 25-35 days with an average of 28.1±2.12 days. Developmental stages observed under a compound microscope were classified based on the changes in the developing eye, such as optic cup, early-eyed, middle-eyed, late-eyed, very late-eyed etc. It was noticed that tail portion comes out first at birth. The number of fry per brood ranged from 12 to 60. New born fries were observed with transparent or blackish in colour having slender body with jaws developed on mouth and were fully capable of swimming, eating, and avoiding danger. Guppy grew rapidly, attained sexual maturity at 8 -10 weeks and reached full size in 6 months. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17866 J. Asiat. Soc. Bangladesh, Sci. 39(2): 259-267, December 2013